Living and dead foraminiferal assemblages of the last decades from Kveithola Trough: Taphonomic processes and ecological highlights - Gamboa-Sojo, Viviana Maria; Husum, Katrine; Caridi, Francesca; Lucchi, Renata G.; Bensi, Manuel; Kovačević, Vedrana; Sabbatini, Anna; Langone, Leonardo; Dominiczak, Aleksander Tadeusz; Povea, Patricia; Morigi, Caterina (Marine micropaleontology, 2021)
We examine the living and dead benthic foraminiferal assemblages from the topmost 10 cm (using 150 μm sieve fraction) of three sedimentological short records collected in the Kveithola Trough (northwest Barents Sea). Our aim is to reconstruct the environmental variations of the last decades, connected to the interaction among the North Atlantic and the Arctic water masses. Our samples are collected at water depths between 150 and 380 m during the Eurofleets2-BURSTER oceanographic cruise, on board of the R/V Polarstern (June 2016). In the Cell Tracker Green (CTG) labelled living foraminiferal fauna, the main species are Pullenia bulloides, Globobulimina auriculata, and Nonionellina labradorica, while in the dead assemblages the main species are Cassidulina neoteretis, Cibicidoides lobatulus, and Cassidulina reniforme (outer, inner, and shelf stations, respectively). The dead foraminiferal assemblages show no significant traceable environmental changes in the Kveithola Trough area occurred during the last ca. 100 years. Conversely, the living foraminiferal fauna shows that this area is subject to variations related to circulation changes and organic matter burial in sediments, to which the biota adapts quickly. Moreover, the species that are only observed in the dead foraminiferal assemblages and not in the living CTG-labelled foraminiferal assemblages (e.g. C. reniforme) are typical of colder water and highlight the ongoing warming of the Arctic area. We find that the preservation of foraminiferal tests may bias the paleontological results. The agglutinated tests are often disintegrated, and the delicate calcareous ones are broken. The environmental conditions (style of sedimentation, bottom currents, interaction with other communities) can weaken the foraminiferal tests and make them prone to breakage or dissolution. •Monitoring recent short and long-term climatic variations in the Kveithola Trough.•Comparison of the living and dead foraminiferal assemblages•Integration of the foraminifera, oceanographic and sedimentological data.•Analysis of taphonomic processes using the living and dead foraminiferal assemblages•Evaluation of bias on the paleocological reconstruction due to taphonomy